Cegah Stunting pada Anak Melalui Edukasi dan Penguatan Pola Asuh Keluarga di Desa Tanjung Dayang Selatan, Kecamatan Indralaya Selatan - Gita Isyanawulan; Dadang Hikmah Purnama; Safira Soraida; Lisya Septiani Putri; Yuanita Dwi Hapsari (Yayasan Pendidikan Penelitian Pengabdian Algero, 2026)
Stunting remains a significant public health issue in Indonesia, primarily due to a lack of public awareness regarding proper parenting practices and optimal child nutrition. This community service program aimed to enhance awareness and understanding, particularly among PKK mothers in Tanjung Dayang Selatan Village, Indralaya Selatan Subdistrict, Ogan Ilir Regency, about the importance of preventing stunting through strengthening family parenting practices. The method employed involved socialization sessions and interactive education using PowerPoint presentations, educational videos, and discussions. A pre-test and post-test were administered to assess participants' knowledge before and after the session. The results showed a significant improvement, with the average pre-test score at 61% and the post-test score increasing to 84%, indicating a better understanding of appropriate parenting practices and the fulfillment of nutritional needs essential for optimal child growth. Additionally, the involvement of university students in this program provided valuable experiential learning in community engagement. Through this initiative, it is expected that the community will be more aware of the critical role families play in preventing stunting, thereby fostering a healthier environment for future generations.